Um estudo da Blockchain aplicado ao contexto dos dados de pesquisa - Ouchi, Marcos Teruo (2019)
The possibility of scientific discussion is the core of the practical research routine and, for this, researchers must find sufficiently detailed resources and descriptions in the published papers in order to obtain the same results within the enough margins of experimental errors. Among the available resources, the data collected during the research e summing it is essential, because the result obtained should be the product of its rigorous analysis. In this scope and associated with distributed consensus mechanisms, the Blockchain data structure can ensure data reliability in a transparent, decentralized and immutable way, and emerges as a possibility to contribute to the progress of science through new ways of processing large amounts of data collected in a scientific research. In this sense, the general objective of this work is to analyze Blockchain technology and its possibilities inserted in scientific communication and research data management. The specific objectives are to describe the management of research data and the data lifecycle; identify the main concepts, structure and functioning, related to Blockchain technology; and point out Blockchain technology and its potential applications in Science. This is an exploratory and theoretical research of qualitative character. The results present the survey conducted on Scientific Communication and its relationship with Information Science, focusing on the importance of data management and metadata for the description of research datasets, and their impact with Blockchain. It is considered that the moment is premature to affirm that Blockchain or any of the technologies in its surroundings, in its current stages, will solve all problems related to the reproducibility crisis. In the short term Blockchain is likely to be applied to specific points in the flow of scientific research helping to resolve mistrust in the data and methodologies used. Since the applications related to the theme are still in embryonic phases of development, implementation and acceptance, it is not even possible to affirm that their implementations are close to the objectives to which they were designed, thus enabling numerous opportunities for research and developments for Information Science.